Controlling Ebola: what we can learn from China's 1911 battle against the pneumonic plague in Manchuria. (April 2015) - Liu, He; Jiao, Mingli; Zhao, Siqi; Xing, Kai; Li, Ye; Ning, Ning; Liang, Libo; Wu, Qunhong; Hao, Yanhua
Highlights: Contrast background environment between the pneumonic plague in Northeast China and Ebola outbreak in West Africa. Summarized the experience of fight against the plague to enlighten the practice of controlling Ebola in details. The height of the government's attention – calling for a strong government. National linkage and strengthening international cooperation–format of a quarantine center. Isolation prevention system. Strict quarantine system. Breaking the traditional concepts and practices. Positive guide from the public media. Summary: The pneumonic plague, which spread across Northeast China during the winter of 1910 and spring of 1911, caused numerous deaths and brought about severe social turmoil. After compulsory quarantine and other epidemic prevention measures were enforced by Dr Wu Lien-teh, the epidemic was brought to an end within 4 months. This article reviews the ways in which the plague was dealt with from a historical perspective, based on factors such as clinical manifestations, duration of illness, case fatality rate, degree of transmissibility, poverty, inadequate healthcare infrastructure, and the region's recent strife-filled history. Similarities were sought between the pneumonic plague in Northeast China in the twentieth century and the Ebola virus outbreak that is currently ravaging Africa, and an effort made to summarize the ways in which specific measures were applied successfully to fight the earlier epidemic. Our efforts highlight valuable experiences that are of potential benefit in helping to fight the current rampant Ebola epidemic in West Africa.